An investigation of the adducts of sulfur tetrafluoride (SF4) with BF3, AsF5, and SbF5. (24th March 2018) - Du, Hongchen; Wu, Jinpeng; Cui, Xin
ABSTRACT: Three adducts SF4 ·BF3, SF4 ·AsF5, and SF4 ·SbF5 were studied in this work, in gas phase, DFT method was performed to study their molecular structures and thermodynamic properties. The heat of formation was studied at the high level DFT levels. Crystal structures were predicted using the Dreiding force field and refined by DFT-GGA-RPBE method. All the obtained crystal structures belong to the P 21 / c space group. The lattice energies were predicted to be located between −91.86 and −693.73 kJ/mol at the GGA-RPBE level. Based on the optimized crystal structures, the band gap (ΔEg) and density of state (DOS) were predicted and the calculations indicate that they are semiconductors with the band gap between 2.22 and 2.43 ev.